Map of vegetation series of Ponza island (central Italy) - Stanisci, Angela; Feola, Silverio; Blasi, Carlo (Lazaroa, 2006)
Cartography, syntaxonomy and syndynamics of plant communities of Ponza island are discussed. Seventeen plant associations have been identified and their successional position was pointed out. Six potential natural vegetation units were described and the different land cover types for each units were mapped (scale 1:10 000, printed at scale 1:25.000) and evaluated. The originality of taxa combination in the plant communities allowed us to propose two new associations, Calicotomo villosae-Rubetum ulmifolii (mantle) and Brassico fruticulosae-Brachypodietum retusi (secondary grassland), as well as two new subassociations. Although the residual woods are very fragmented and need a special protection against fires for their survival, the Ponza landscape has an important naturalistic and ecological value due to its high diversity of plant taxa and plant communities.